2017
DOI: 10.4049/jimmunol.1601822
|View full text |Cite|
|
Sign up to set email alerts
|

Green Tea Polyphenol EGCG Upregulates Tollip Expression by Suppressing Elf-1 Expression

Abstract: TLR signaling is critical to innate immune system regulation; however, aberrant TLR signaling is involved in several diseases, including insulin resistance, Alzheimer's disease, and tumor metastasis. Moreover, a recent study found that TLR-4 signaling pathway inhibition might be a target for the suppression of chronic inflammatory disorders. In this article, we show that the green tea polyphenol epigallocatechin-3--gallate (EGCG) increases the expression of Toll interacting protein, a strong inhibitor of TLR4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 43 publications
2
17
0
Order By: Relevance
“…For attributed concentrations of KEGG pathways of various time levels with GTP intervention, the dominant statistical differences should be concentrated on transcription, material supply, as well as excretory system. However, for KEGG pathway investigation on different expressed genes, although the ranking differed with time, ABC transporters and amino acids biosynthesis occupied the top classes during every stage, showing that GTP pretreatment influenced above‐mentioned pathways substantially, which needs further investigation (Kumazoe, Yamashita, et al, ). TLR signaling is critical to innate immune system regulation, however, aberrant TLR signaling is related to several diseases, such as insulin resistance, Alzheimer’s disease, and tumor metastasis.…”
Section: Expound the Influence Of Egcg And Intestinal Flora On Host Hmentioning
confidence: 99%
“…For attributed concentrations of KEGG pathways of various time levels with GTP intervention, the dominant statistical differences should be concentrated on transcription, material supply, as well as excretory system. However, for KEGG pathway investigation on different expressed genes, although the ranking differed with time, ABC transporters and amino acids biosynthesis occupied the top classes during every stage, showing that GTP pretreatment influenced above‐mentioned pathways substantially, which needs further investigation (Kumazoe, Yamashita, et al, ). TLR signaling is critical to innate immune system regulation, however, aberrant TLR signaling is related to several diseases, such as insulin resistance, Alzheimer’s disease, and tumor metastasis.…”
Section: Expound the Influence Of Egcg And Intestinal Flora On Host Hmentioning
confidence: 99%
“…Activation of HB-8902 © by PPIs also promotes molecular changes -P63151, P61088, P08238, P04899, Q15185 -in 'Toll interacting proteins' [36,37] and downstream effectors of TLR4-associated molecules such as CD36 and members of it's signaling pathway [38]. These contribute to the negative regulation of TGF-β1-mediated activation of Smad signaling pathways [28] and the endogenous production of anti-inflammatory agents modulating TLR4 linked cytokine synthesis [39].…”
Section: Phenotypic Changesmentioning
confidence: 99%
“…[ 5–9,20 ] 67LR has also been shown to confer EGCG responsiveness to cancer cells at physiological concentrations [ 5,6,9,10,21–25 ] and to mediate the beneficial activities of EGCG, which include anti‐atherosclerosis, insulin‐sensing modulation, anti‐allergic, and anti‐inflammatory activities. [ 26–31 ] However, (−)‐epicatechin‐3‐ O ‐gallate, a similar compound to EGCG that lacks one hydroxyl group in comparison, could not activate 67LR. Consistent with those results, our study shows that PC1 also acts as the ligand for 67LR, whereas PB1/2 dose not interact with 67LR.…”
Section: Discussionmentioning
confidence: 99%
“…We previously reported that 67LR‐dependent signaling plays the crucial role in several beneficial effects including anti‐inflammatory and anti‐allergic activities of EGCG. [ 30,31 ] Considering the effect of PC1 on 67LR‐dependent signaling, the anti‐inflammatory effect of PC1 [ 43 ] could be mediated by 67LR activating signaling.…”
Section: Discussionmentioning
confidence: 99%